Life Cycle Perspective for Urban Energy Use and Carbon Emissions: A Case Study of Xiamen, China - Meng, Fanxin; Liu, Gengyuan; Yang, Zhifeng; Hao, Yan; Zhang, Yan; Ulgiati, Sergio (Journal of Environmental Accounting and Management, 2026)
Low-carbon city is the key to achieving low-carbon future. Carbon emission accounting is the most fundamental step. Carbon emissions from urban energy use are the principal and key bodies of global carbon emissions reduction, which are the most important parts of urban carbon emissions. The goal of this study is to construct a novel hybrid analysis model framework (PEIO), a combination of Process Analysis (PA) and Environmental Input-Output Analysis (EIOA), to access the carbon emissions on urban energy use from life cycle perspective, including the carbon emissions from end-use sector activities, cross-boundary traffic and the embodied energy of key urban materials.